Heterogeneous lupus-specific lesions and treatment outcome, in a single patient, over a period of time - Fernandes, M (2019)
The report highlights the importance of strict clinico-histological correlations when skin biopsies are performed in diagnostic doubt in systemic lupus erythematosus. Furthermore, PUVA is never indicated in autoimmune conditions involving photosensitivity, due to high potential for internal and cutaneous aggravation of the disease, as the authors observed in this case.